PKM Pendampingan Kelengkapan Administrasi Platform Merdeka Mengajar Di Paud Gilang Dan Paud Aiza Desa Kelobak Kabupaten Bengkulu Tengah - Handayani, Tuti; Saputra, Harius Eko; Yusuarsono, Yusuarsono; Larasati, Jesica Fitria; Sintia, Nopa (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
The Community Service Activity (PKM) was carried out by a lecturer in the Public Administration Study Program at DEHASEN BENGKULU UNIVERSITY in April 2022 in PAUD Gilang and PAUD Aiza, Kelobak Village, Central Bengkulu Regency. This activity aims to improve the ability of teachers in completing learning administration through the use of the Merdeka Teaching Platform (PMM) as part of the implementation of the Merdeka Learning policy. The main problems faced by the two PAUD institutions are the limitations of digital literacy, the not optimal filling in administrative documents in PMM, as well as lack of technical assistance in the management of digital -based administration. The method of implementing activities includes the preparation, training and technical assistance stages, evaluation, and reflection of the results of the activity. The approaches used are participatory and applicative, with direct guidance in making accounts, filling in data, and uploading learning documents such as daily activity plans (RKH), journal activities, and child development reports. Activities results show significant increases in the ability of teachers in operating PMM and completing digital learning administration documents. In addition, this activity succeeded in fostering awareness of the importance of orderly administration, efficiency of document management, and accountability of educational institutions. This activity also strengthens the synergy between universities and basic educational institutions in supporting digital transformation of education in rural areas.